HUMAN RESOURCE MANAGEMENT - Rahman, Yudi Ardian (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2022)
In the Islamic perspective, education has played an important role in efforts to produce reliable human beings who can answer the challenges of the times. Human Resources (HR) have a central position in realizing development performance, which places humans in their function as development resources. Human resources are instrumental in determining the progress of a country. The existence of the Indonesian nation in the midst of the current global era will be influenced by the ability of Indonesian human resources, especially those characterized by the ability to master science and technology and strengthen faith and piety towards God Almighty. One of the important resources in management is human resources. Keywords: Human Resource Management